1986
DOI: 10.1111/j.1442-9993.1986.tb01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the abundance and body condition of honeyeaters (Meliphagidae) in response to inflorescence and nectar availability in the New England National Park, New South Wales

Abstract: Seasonal changes in numbers and body condition of honeyeaters were examined over 2 years in the New England National Park, New South Wales, Australia. Nectar availability measured as inflorescence density and nectar production were also recorded. In the main study site, the abundance of six of the seven most common species ofhoneyeater was significantly correlated with inflorescence density. However, honeyeater numbers were not significantly correlated with daily energy productivity. Unlike most honeyeater com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…McFarland (1986) found that many species increased in body mass and fat deposits during autumn and remained at their heaviest throughout late autumn and winter. Hence, this pattern appears to be relatively common amongst this family in temperate climates.…”
Section: Body Mass and Fat Depositionmentioning
confidence: 98%
“…McFarland (1986) found that many species increased in body mass and fat deposits during autumn and remained at their heaviest throughout late autumn and winter. Hence, this pattern appears to be relatively common amongst this family in temperate climates.…”
Section: Body Mass and Fat Depositionmentioning
confidence: 98%
“…However, these studies were not designed to measure changes in the aggressiveness of the birds toward one another and did not attempt to distinguish between the many factors that could account for changes in amounts of aggression observed. Changes in nectar availability are often accompanied by changes in abundance and species composition of honeyeaters (Ford and Pursey 1982;Ford 1983;Collins et al | 984;Ford and Paton 1985;Newland and Wooller 1985;Pyke 1985;McFarland 1986c;Pyke and Recher 1988;Ramsey 1989) and may be accompanied by changes in age structure, sex ratio, and activity patterns. Any of these factors could alter the number of aggressive acts per time or the proportions of time budgets spent on aggression.…”
Section: Introductionmentioning
confidence: 99%
“…The diseased sites clearly showed that there was an almost complete loss of the dominant overstorey Banksia (a very important source of nectar for birds in these woodlands) and a reduction in the flowering of understory plants. Although we did not measure actual nectar content, it is a reasonable assumption that flower availability is strongly correlated to nectar availability (McFarland, 1986). Given the importance of Banksia species for nectarivorous birds in our study system (Newland and Wooller, 1985;Ramsey, 1989), and that seasonal flowering events can lead to densities of nectarivorous birds that are much higher than surrounding areas (Newland and Wooller, 1985), the ongoing loss of Banksia species due to P. cinnamomi is a major concern.…”
Section: Are Changes In the Bird Community Related To Dieback-inducedmentioning
confidence: 99%
“…Nectar availability is a key driver of population dynamics in bird communities dominated by nectarivores such as in south-western Australia (McFarland, 1986;Newland and Wooller, 1985) and South Africa (Symes et al, 2008). Although previous studies have suggested a potential impact of P.…”
Section: Are Changes In the Bird Community Related To Dieback-inducedmentioning
confidence: 99%